Per una grammatica del sogno nel «Decameron». Forme e strutture delle novelle a tema onirico - Artico, Tancredi (Italianistica Debreceniensis, 2018)
This paper takes into account the oneiric issue in Giovanni Boccaccio Decameron, with the aim of defining Boccaccio’s overall “grammar of dreaming”: besides an accurate investigation on Decameron’s sources, which range from classic to Medieval literature, it retraces the narrative constructions of the short-novels with oneiric subjects, hypothesizing the existence of two main schemes. In the short-tales on a vision (which are the most known), it is almost always replied the scheme of the “tale in the tale”, due to the creation of a imaginary world with its own rules. Meanwhile, in the short tales of deceiving, the dream is useful to trick the naive antagonist, making him believe something unbelievable. In both cases, it has a deep influence on the so-called “statute of reality” (Amedeo Quondam): in the first, there is the invention of a new reality; in the second it is deconstructed instead.